DAMPAK GLOBALISASI TERHADAP BUDAYA LOKAL DI KALANGAN REMAJA SISWA KELAS XI SMAN 1 BENGALON - Mukhlas Alkadri; Hj.Fatimah Azis (STKIP Subang, 2024)
This article discusses the impact of globalization on local culture among XI-grade students at SMAN 1 Bengalon, from a sociological perspective. Utilizing a qualitative approach, the study adopts a case study design that involves in-depth interviews and participatory observations. A total of 20 students were purposively selected to explore their views on the influence of globalization on their cultural mindset and behaviors. Data collection was carried out through semi-structured interviews focusing on students' personal experiences with foreign cultures as well as their perceptions of local culture. Participatory observations were conducted during extracurricular activities, such as dance and music, to understand social interactions and cultural dynamics among the students. Actions taken during the research included data collection through group discussions and forums, allowing students to share their perspectives and deepen their understanding of their cultural identities. From a sociological perspective, globalization acts as a process of social interaction that brings together various cultures but also threatens the survival of local culture. The findings indicate that although globalization enhances access to information and cultural exchange, there are risks of local cultural erosion and identity crises among students. This research emphasizes the importance of education in preserving local culture, recommending the integration of cultural values into the curriculum and extracurricular activities. The results are expected to provide insights for educators and policymakers regarding effective strategies for maintaining local cultural sustainability amid the increasing influence of globalization.